Inovasi Pengelolaan Pesantren dalam Menghadapi Persaingan di Era Globalisasi - Damanhuri, Ahmad; Mujahidin, Endin; Hafidhuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2013)
Pesantren as an informal institution of education has been growing from recent years. Nowadays, the development of pesantren has been progressed. In these days, most people know Pesantren because of its success in making our nations have a better generations. Pesantren has gotten many respect from the society and another formal institutions because of their organized and neatly plans in their programs. Regardless of whether it is possible or not that their format and concept of education have been found, this phenomenon clearly indicates that the symptoms to establish Pesantren educational institutions are interesting to study.Generally, this study is having a goal to describe integrated boarding innovation management in Pesantren Terpadu and Pesantren at al-Karimiyah Darussalam and to acknowledge the format of an ideal concept of integrated management of schools in both of Pesantren. The design of this study is using a qualitative approachment with multicases design. In this study, our data have been collected through interviews, participant observation and documentation. The results of this study indicated the existence of an integrated management of Pesantren in Al-Karimiyah boarding schools and Daarussalam boarding schools. Both schools are also incorporate the concept of curriculum of the National Education Ministry and Religion Ministry, while maintaining the tradition of reviewing the books of yellow as a characteristic of the Pesantren. Pesantren Al-Karimiyah managed their education and their technique of teaching by assimilating the three systems of education management, such as management of education based on the Ministry of Religion curriculum, education management based on Pesantren Salaf, and management of education that refers to the modern Pesantren Gontor. Based on that three types of management education assimilation, They are synthesized into a pattern of innovation management education and technique of teaching which are interesting to study. With their way, Pesantren Al-Karimiyah and Daarussalam are able to make their education and technique of teaching more vibrant and competitive with the times.